The effects of 16 weeks of intensive cycling training on seminal oxidants and antioxidants in male road cyclists - Maleki, B. H.; Tartibian, B.; Vaamonde, D. (Clinical Journal of Sport Medicine, 2014)
Objective: To examine the effects of 16 weeks of intensive cycling training on seminal reactive oxygen species (ROS), malondialdehyde (MDA), superoxide dismutase (SOD), catalase, and total antioxidant capacity (TAC) in male road cyclists. Design: Repeated measures design. Setting: The Exercise Physiology Laboratory of the Urmia University. Participants: Twenty-four healthy nonprofessional male road cyclists (aged 17-26 years) participated in this study. Interventions: All subjects participated in 16 weeks of intensive cycling training. The semen samples were collected, respectively, at baseline (T1), immediately (T2), 12 (T3), and 24 (T4) hours after the last training session in week 8; immediately (T5), 12 (T6), and 24 (T7) hours after the last training session in week 16; and 7 (T8) and 30 (T9) days after the last training session in week 16. Main Outcome Measures: Total antioxidant capacity and SOD were measured by colorimetric assay. The levels of ROS were measured by a chemiluminescence assay. Malondialdehyde levels were measured by thiobarbituric acid reactive substance assay. Catalase was measured by monitoring the initial rate of disappearance of hydrogen peroxide (initial concentration 10 mM) at 240 nm. Results: The levels of seminal ROS and MDA increased (P < 0.008) and remained high after 30 days of recovery. The levels of seminal SOD, catalase, and TAC decreased (P < 0.008) and remained low after 30 days of recovery (P < 0.008). Conclusions: Sixteen weeks of intensive cycling training may have deleterious consequences for spermatozoa and hence may affect sperm healthy parameters in male cyclists.